Optimization of the primary nursing care model to improve the quality of nursing services: Optimalisasi implementasi model asuhan keperawatan profesional metode primer dalam peningkatan mutu pelayanan keperawatan - Linda, Baiq; Mardiati; Dodi Wijaya; Dewa, Dewa Gede Sanjaya Putra (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2026)
The Professional Nursing Care Model (PNCM) using the primary method emphasizes patient-centered care by assigning one primary nurse with full responsibility for managing comprehensive nursing services throughout a patient’s hospitalization. However, its implementation in inpatient units has not been fully optimal, as reflected in issues related to continuity of care, unclear role distribution, and the absence of standardized operational guidelines. This community service initiative aimed to optimize the implementation of the PNCM–Primary Method to enhance the quality of nursing services in inpatient settings. The program was conducted through several stages, including situational analysis, development and implementation of standardized operational procedures (SOPs), structured role assignment for primary nurses, and continuous training and mentoring. Evaluation methods included direct observation, feedback from nursing staff, and audits of nursing documentation. The results indicated notable improvements in the continuity and coordination of care, increased accuracy and completeness of nursing documentation, and higher patient satisfaction levels. Nurses also demonstrated improved understanding of their roles, stronger accountability, and more effective communication within interprofessional teams. Additionally, the establishment of clear guidelines supported consistency in care delivery. In conclusion, optimizing the PNCM–Primary Method effectively improved the quality of nursing services, strengthened professional responsibility, and promoted a more patient-centered approach. This model is recommended for sustained implementation across inpatient units as part of ongoing quality improvement and accreditation readiness efforts.